The Selves of Social Animals: Comments on Gruen. (September 2014) - Shoemaker, David
Abstract: In this commentary on Lori Gruen's "Death as a Social Harm, " I first lay out the basics of Gruen's argument, then I offer some critical discussion, and finally I explore whether there might be some metaphysical structure that would support her most provocative idea—that death harms our social selves . What would it take for this idea to be more than metaphor, so that when a loved one dies a part of me has died? In constructing one possibility, I draw from the distinction between identity and what matters in identity to paint a picture of social selves whose relationships are constructed out of the tendrils of psychological connectedness and continuity that serve to unite different stages of single persons. I conclude by exploring whether this metaphysical picture is sufficient to generate the conclusions at which Gruen aims.